Insulin glargine 300 U/mL and insulin degludec: A review of the current evidence comparing these two second‐generation basal insulin analogues. Issue 7 (11th June 2020) - Cheng, Alice; Bailey, Timothy S.; Mauricio, Didac; Roussel, Ronan
Summary: For most people with type 2 diabetes (T2D), treatment intensification with the addition of basal insulin therapy is required to maintain glycaemic control. However, this often does not happen in real‐life practice promoting the development of long‐term diabetes‐related complications. The second‐generation basal insulin analogues glargine 300 U/mL (Gla‐300) and degludec (IDeg) provide pharmacokinetic and pharmacodynamic improvements that may allow them to be more effective in appropriately managing diabetes compared with first‐generation basal insulin analogues. Both Gla‐300 and IDeg have been extensively studied vs the first‐generation basal insulin glargine 100 U/mL, demonstrating comparable efficacy in terms of glycaemic control, and a lower risk of hypoglycaemia. The BRIGHT randomized controlled trial is the first direct comparison of the efficacy and safety profiles of Gla‐300 and IDeg in patients with T2D. Moreover, real‐world data have been used to assess the effectiveness of these basal insulins during routine clinical practice. Further research is required to determine if the properties of Gla‐300 and IDeg may lead to improvements in healthcare‐related costs and the quality of life of patients, which are important factors for informing clinical decisions.